The Age Limit for Presidential and Vice-Presidential Candidates in Constitutional Court: An Implication of Ethical Sanctions for Judges - Fauzan, Muhammad; Iriani, Dewi; Budiono, Arief; Rannie, Mahesa; Marvinda, Elsa Sintya (Faculty of Law, Universitas Jenderal Soedirman, 2024)
Almas filed a lawsuit to change the minimum age of presidential and vice presidential candidates from 40 years to 35 years. Almas believed that if it is not changed, it will be contrary to the Republic of Indonesia’s 1945 Constitution. This decision is controversial but has opened a rare opportunity for talented young people to ascend and hold presidential and vice-presidential positions via election, even when they are less than 40 years old. The Republic of Indonesia’s Constitutional Court judges partially accepted Almas' lawsuit, in which the age limit remains at least 40. However, it can be deviated if a person has had experience becoming a regional head (governor/regent/mayor). This research aims to analyze: (1) how Constitutional Court judges interpret the minimum age limit for presidential and vice-presidential candidates in the Indonesian constitutional system; and (2) how the Constitutional Court judges’ final authority, which is Decision No.90/PUU-XXI/2023 on the Minimum Age Limit for Presidential Candidates and Vice-Presidential Candidates is a controversial decision. Method: This study used a jurisprudence approach, which studied the judicial decision in court primary data. It was supported by secondary data, which were obtained through a literature review. It focused on the data of Decision No. 90/PUU-XXI/2023, the Indonesian Constitution, and the Election Law (2017). Findings: In this study, it was found that the Decision of the Constitutional Court No. 90/PUU-XXI/2023 on the Minimum Age Limit for Presidential and Vice-Presidential Candidates is controversial, considering how the judge decided it. Then, several judges were sentenced for the act of ethics violation by the Constitutional Court’s Honorary Assembly. Conclusion: The decision of the Constitutional Court is binding and final, even though it is controversial. Several judges were sentenced for committing a violation of ethics by the Constitutional Court’s Honorary Assembly. Even so, this decision also opened up an opportunity for talented but young people under 40 to become presidential or vice-presidential candidates in the election.Keywords: Reconstruction, Age Limit, Presidential Candidates, Vice-Presidential Candidates